On the behavior of solutions of the equation for components of a normal system of differential equations - Yanchuk, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We obtain necessary and sufficient conditions for the existence of a sliding mode and also for the knotting of solutions of the equation for components of a normal system of first-order differential equations.